2019
DOI: 10.1111/ijpo.12508
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents' exposure to food and beverage marketing in social media apps

Abstract: Summary Background Unhealthy food marketing is a powerful determinant of unhealthy diets and obesity among children. Although it is known that food marketers target young people on social media, no study has yet quantified children's exposure on these platforms. Objectives To compare the frequency and healthfulness of food marketing seen by children and adolescents on social media apps as well as estimate their weekly exposure. Methods 101 children and adolescents (ages 7‐16 years) completed a survey on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(175 citation statements)
references
References 33 publications
11
114
3
Order By: Relevance
“…These findings have interesting implications for the regulation of advertising disclosures. Not only do many influencers fail to comply with the rules [20,88,89], but many children in the current study did not consider advertising disclosures to have any real significance in determining their attitude towards the promoted product. This is likely why research shows advertising disclosures have no protective impact on children's (9-11-years) immediate intake when featured during influencer marketing of an HFSS product [22].…”
Section: Theme 4: Attitudes Towards Influencer Marketing Are Most Affmentioning
confidence: 84%
See 3 more Smart Citations
“…These findings have interesting implications for the regulation of advertising disclosures. Not only do many influencers fail to comply with the rules [20,88,89], but many children in the current study did not consider advertising disclosures to have any real significance in determining their attitude towards the promoted product. This is likely why research shows advertising disclosures have no protective impact on children's (9-11-years) immediate intake when featured during influencer marketing of an HFSS product [22].…”
Section: Theme 4: Attitudes Towards Influencer Marketing Are Most Affmentioning
confidence: 84%
“…Children's beliefs about the likely effects of influencer marketing are consistent with advertisers' increased spend in this area [17,18] and as result of this fast-growing industry children are frequently exposed to influencer marketing of HFSS food and beverage products [14,[19][20][21].…”
Section: Theme 4: Attitudes Towards Influencer Marketing Are Most Affmentioning
confidence: 98%
See 2 more Smart Citations
“…The marked growth in social media–based marketing may greatly increase overall exposure to food, beverage, and snack ads, particularly among youth. Although no studies have comprehensively examined youth exposure to food and beverage advertising on social media, researchers in one cross‐sectional study estimated ad exposure by asking 101 children and adolescents ages 7 to 16 years to screen record their activity on their favourite social media app for a 5‐minute period . They found that 72% of participants were exposed to ads on social media during the data collection period, with the majority of ads promoting unhealthy foods and beverages.…”
Section: Discussionmentioning
confidence: 99%